Spirit of place and the evolution of the vernacular house in Kinnaur, Himachal Pradesh, India - Belz, Melissa Malouf (Kansas State University, 2012)
India is a country rich in religious beliefs, with a cultural landscape infused with symbolic meaning. The nation is currently experiencing great advances in development, standard of living, and connectedness to global markets and cultures. For remote communities, the spread of global ideas can significantly impact traditional customs and distinctive landscapes. Vernacular houses, meaning those particular to a region and culture, and built with local ingenuity, are vital contributors to sense of place and cultural identity. India’s remote mountainous regions in particular, are at a threshold of change in the vernacular landscape. Therefore, my dissertation focuses on Kinnaur district, of Himachal Pradesh, a remote folk region of the Indian Himalaya with a strong vernacular heritage and potential for great change in its cultural landscape. Because architecture is culturally significant and provides a clear medium in which to see changes in the landscape, the purpose of this research is (1) to determine the characteristic features of the Kinnauri vernacular house, (2) to identify the reasons for and process of vernacular landscape change, and (3) to illustrate the potential of decorative or small-scale features as significant components of place-making and enduring vernacular landscapes. My methods consisted of historical archives, landscape analysis (direct observation, photography, and drawings), and open-ended in-depth interviews with homeowners, builders, and officials. Through these methods, I distilled the characteristics of the Kinnauri vernacular house to eight distinguishing architectural features and determined the three most influential agents that directly impact landscape change and the vernacular house. My final conclusions recognize a paradox in landscape identity and that small-scale features are significant components in place-making. Furthermore, my research highlights the crucial role of ensembles and adaptability in enduring vernacular landscapes. Although homogenization of landscapes is evident across the globe, many places still exhibit individualized characteristics and cultural identity. I contend that the increased ability of small-scale architectural features to adapt to new settings, allows a modernizing landscape to preserve aspects of the vernacular architecture.
Keywords: Cultural landscape; Vernacular house; Globalization; India; Himalaya; Architecture (0729); Geography (0366); Landscape Architecture (0390)